ANALISIS KELAYAKAN USAHA DAN SELEKTIVITAS PURSE SEINE KAPAL 30 GT DI PERAIRAN SIBOLGA PROVINSI SUMATERA UTARA - Indah Sartika; Yoes Soemaryono; Amanatul Fadhilah (AQUACOASTMARINE, 2017)
Analysis of business feasibility and selectivity of purse seine gear vessels of 30 GT determines that a fishery business can be developed because it has a profit, or in the business can not continued because the business result have a loss. The purpose of this research is to know description of purse seine gear, to know the business feasibilityby counting value productivity, analyze the financial and technical aspects, to know selectivity of purse seine gear on the catch vessel of 30 GT in Sibolga waters North Sumatera Province. The results of the research the length of purse seine nets for 30 GT boats of about 300 – 500 m were called of Rapat Trawls. The purse seine around Rp 586,508,000 up to Rp 845,174 per year and quite profitable. The purse seine mesh size of the cod 2 cm selective size to the type of Layang fish (Decapterus spp.) 8,573 tails or 22,4%, the fork length size were 20.0 up to 30.0 cm, average size were 25,525 cm. Cakalang fish (Katsuwonus pelamis) that were 3,300 tails or 8.6%, the fork length size were 25.0 up to 40.0 cm, average size were 31,061 cm and Kembung fish (Ratrelliger spp.) that were 4,215 tails or 11,02%, the fork length size were 15,0 up to 26.0 cm.Keywords: Sibolga Waters, Business Feasibility, Profitable, Selectivity, Purse Seine, Vessel 30 GT, North Sumatera Province.